Effect of zinc oxide nanoparticles on the flexural strength of polymethylmethacrylate denture base resin - N. Gopi Chander; Santhanam Vıkram (Istanbul University, 2020)
Purpose This study evaluated the flexural strength of polymethyl methacrylate (PMMA) reinforced with various concentrations of zinc oxide (Zn O) nanoparticles Materials and Methods Nano ZnO was added in 0, 0.4, 0.6, 0.8, 1.2 and 1.4 percentage to PMMA denture base material. 60 specimens of heat cure polymerizing acrylic resin of dimensions 10mm x 4mm x 80mm were fabricated in accordance to ISO 20795-1-2013. The specimens were divided into 6 groups. Acrylic specimens were processed according to manufacturer's instruction. Three-point bending test was performed to evaluate the flexural strength. Surface analysis was performed with scanning electron microscopy (SEM) to observe the fracture surfaces of specimens. ANOVA and Tukey tests were used for the statistical analysis (p < 0.05). Results Statistical analysis revealed significant differences in strength between groups. The flexural strength improved with the addition ZnO nanoparticles. Highest mean value was observed in Group nZn -14 (91.31 MPa) and lowest in control Group nZn-0 (61.36 MPa). ANOVA and Tukey's honestly significance test found statistical significant differences among the groups ( p<0.001). Conclusion The addition of ZnO nanoparticles in all concentrations increased the flexural strength of acrylic resin when compared to the control group.